2012
DOI: 10.1089/hum.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Ras-Transfected, EBV-Transformed Lymphoblastoid Cell Lines as a Model Tumor Vaccine for Boosting T-Cell Responses Against Pancreatic Cancer: A Pilot Trial

Abstract: Genetically modified lymphoblastoid cell lines (LCL) have been shown to be an attractive alternative source of antigen-presenting cells for cancer vaccination in vitro. We tested their application in patients with pancreatic cancer in a phase I clinical trial. As a model tumor antigen, we selected the point-mutated (codon 12) Ki-Ras p21 oncogene (muRas) frequently (∼85%) present in pancreatic adenocarcinoma. Autologous LCLs were established in vitro by spontaneous outgrowth from peripheral blood lymphocytes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…LCLs have a high immunostimulatory capacity and can be easily and largely obtained by rapid and long‐lasting growth in vitro , and thus they are potentially unlimited sources of potent APCs to prime either CD4 + or CD8 + for immunotherapy. Indeed, several studies reported that LCLs pulsed ex vivo with neoantigens or other tumor‐associated antigens could induce specific anti‐tumor immunity . However, in addition to EBV‐associated antigens, nonsynonymous mutations arising in high‐passage LCLs could also induce activation and proliferation of nonspecific T cells, which theoretically result in obscuring the detection of tumor‐specific T‐cell response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCLs have a high immunostimulatory capacity and can be easily and largely obtained by rapid and long‐lasting growth in vitro , and thus they are potentially unlimited sources of potent APCs to prime either CD4 + or CD8 + for immunotherapy. Indeed, several studies reported that LCLs pulsed ex vivo with neoantigens or other tumor‐associated antigens could induce specific anti‐tumor immunity . However, in addition to EBV‐associated antigens, nonsynonymous mutations arising in high‐passage LCLs could also induce activation and proliferation of nonspecific T cells, which theoretically result in obscuring the detection of tumor‐specific T‐cell response.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expense and complexity of obtaining sufficient dendritic cells due to low frequency in peripheral blood and in vitro proliferation capacity of dendritic cells has limited its wide application, particularly in critically ill cancer patients . Alternatively, Epstein–Barr virus (EBV)‐transformed B‐lymphoblastoid cell lines (LCLs) have been demonstrated to be excellent professional APCs and most importantly, LCLs could be easily obtained by culturing peripheral blood lymphocytes from EBV‐positive humans in vitro or by incubating with B95‐8 cell supernatant . However, neoantigen‐loaded LCLs could stimulate not only neoantigen‐specific T cells but also nonspecific T cells, which could be due to expression of both EBV antigens and endogenous nonsynonymous mutations arising in LCLs .…”
Section: Introductionmentioning
confidence: 99%
“…Main indication is PDAC at an advanced stage (locally advanced and/or metastatic) with phases 1 and 2 trials and one phase 3 [101,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146]. Three types of strategies have been conducted: in situ gene therapy product injection (by means of EUS), vaccination (intradermal or subcutaneous route) and oncolytic virus administration.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…LCL have been used as APC for the presentation of tumor antigens in vaccination studies [11,17]. In these studies, spontaneously outgrown LCL have been used.…”
Section: Introductionmentioning
confidence: 99%